Cascade of care during the first 36 months of the treatment as prevention for hepatitis C (TraP HepC) programme in Iceland: a population-based study. (August 2021) - Olafsson, Sigurdur; Fridriksdottir, Ragnheidur H; Love, Thorvardur J; Tyrfingsson, Thorarinn; Runarsdottir, Valgerdur; Hansdottir, Ingunn; Bergmann, Ottar M; Björnsson, Einar S; Johannsson, Birgir; Sigurdardottir, Bryndis; Löve, Arthur; Baldvinsdottir, Gudrun E; et al.
Summary: Background: WHO has set targets to eliminate hepatitis C virus (HCV) infection as a global health threat by 2030 through a 65% reduction in HCV-related deaths and 80% reduction in HCV incidence. To achieve these goals, WHO set service coverage targets of 90% of the infected population being diagnosed and 80% of eligible patients being treated. In February, 2016, Iceland initiated a nationwide HCV elimination programme known as treatment as prevention for hepatitis C (TraP HepC), which aimed to maximise diagnosis and treatment access. This analysis reports on the HCV cascade of care in the first 3 years of the programme. Methods: This population-based study was done between Feb 10, 2016, and Feb 10, 2019. Participants aged 18 years or older with permanent residence in Iceland and PCR-confirmed HCV were offered direct-acting antiviral (DAA) therapy. The programme used a multidisciplinary team approach in which people who inject drugs were prioritised. Nationwide awareness campaigns, improved access to testing, and harm reduction services were scaled up simultaneously. The number of infected people in the national HCV registry was used in combination with multiple other data sources, including screening of low-risk groups and high-risk groups, to estimate the total number of HCV infections. The number of people diagnosed, linked to care, initiated on treatment, and cured were recorded during the study. This study is registered with ClinicalTrials.gov, NCT02647879 . Findings: In February, 2016, at the onset of the programme, 760 (95% CI 690–851) individuals were estimated to have HCV infection, with 75 (95% CI 6–166) individuals undiagnosed. 682 individuals were confirmed to be HCV PCR positive. Over the next 3 years, 183 new infections (including 42 reinfections) were diagnosed, for a total of 865 infections in 823 individuals. It was estimated that more than 90% of all domestic HCV infections had been diagnosed as early as January, 2017. During the 3 years, 824 (95·3%) of diagnosed infections were linked to care, and treatment was initiated for 795 (96·5%) of infections linked to care. Cure was achieved for 717 (90·2%) of 795 infections. Interpretation: By using a multidisciplinary public health approach, involving tight integration with addiction treatment services, the core service coverage targets for 2030 set by WHO have been reached. These achievements position Iceland to be among the first nations to subsequently achieve the WHO goal of eliminating HCV as a public health threat. Funding: The Icelandic Government and Gilead Sciences.